Andreev Interference in the Surface Accumulation Layer of Half‐Shell InAsSb/Al Hybrid Nanowires. Issue 11 (5th February 2022) - Stampfer, Lukas; Carrad, Damon J.; Olsteins, Dags; Petersen, Christian E. N.; Khan, Sabbir A.; Krogstrup, Peter; Jespersen, Thomas S.
Abstract: Understanding the spatial distribution of charge carriers in III–V nanowires proximity coupled to superconductors is important for the design and interpretation of experiments based on hybrid quantum devices. In this letter, the gate‐dependent surface accumulation layer of half‐shell InAsSb/Al nanowires is studied by means of Andreev interference in a parallel magnetic field. Both uniform hybrid nanowires and devices featuring a short Josephson junction fabricated by shadow lithography, exhibit periodic modulation of the switching current. The period corresponds to a flux quantum through the nanowire diameter and is consistent with Andreev bound states occupying a cylindrical surface accumulation layer. The spatial distribution is tunable by a gate potential as expected from electrostatic models. Abstract : Understanding the spatial distribution of charge carriers in III–V nanowires proximity coupled to superconductors is important for the design and interpretation of experiments based on hybrid quantum devices. The gate‐dependent surface accumulation layer of half‐shell InAsSb/Al hybrid nanowires is studied by means of Andreev interference in a parallel magnetic field.